Risk of conversion from mild cognitive impairment to dementia in low‐ and middle‐income countries: A systematic review and meta‐analysis. Issue 1 (13th March 2022) - McGrattan, Andrea M.; Pakpahan, Eduwin; Siervo, Mario; Mohan, Devi; Reidpath, Daniel D.; Prina, Matthew; Allotey, Pascale; Zhu, Yueping; Shulin, Chen; Yates, Jennifer; Paddick, Stella‐Maria; Robinson, Louise; et al.
Abstract: Introduction: With no treatment for dementia, there is a need to identify high risk cases to focus preventive strategies, particularly in low‐ and middle‐income countries (LMICs) where the burden of dementia is greatest. We evaluated the risk of conversion from mild cognitive ompairment (MCI) to dementia in LMICs. Methods: Medline, Embase, PsycINFO, and Scopus were searched from inception until June 30, 2020. The search was restricted to observational studies, conducted in population‐based samples, with at least 1 year follow‐up. There was no restriction on the definition of MCI used as long as it was clearly defined. PROSPERO registration: CRD42019130958. Results: Ten thousand six hundred forty‐seven articles were screened; n = 11 retained. Of the 11 studies, most were conducted in China ( n = 7 studies), with only two studies from countries classified as low income. A qualitative analysis of n = 11 studies showed that similar to high‐income countries the conversion rate to dementia from MCI was variable (range 6 . . 0%–44 . . 8%; average follow‐up 3 . . 7 years [standard deviation = 1 . . 2]). A meta‐analysis of studies using Petersen criteria ( n = 6 studies), found a pooled conversion rate to Alzheimer's disease (AD) of 23 . . 8% (95% confidence interval = 15 . . 4%–33.4%); approximately one in four people with MCI were at risk of AD in LMICs (over 3 . . 0–5 . . 8 years follow‐up). Risk factors for conversion from MCI to dementia included demographic (e.g., age) and health (e.g., cardio‐metabolic disease) variables. Conclusions: MCI is associated with high, but variable, conversion to dementia in LMICs and may be influenced by demographic and health factors. There is a notable absence of data from low‐income settings and countries outside of China. This highlights the urgent need for research investment into aging and dementia in LMIC settings. Being able to identify those individuals with cognitive impairment who are at highest risk of dementia in LMICs is necessary for the development of risk reduction strategies that are contextualized to these unique settings.